Manajemen Strategis dan Perencanaan Strategis Pendidikan Islam: Konsep, Urgensi, dan Tantangan Penerapannya - Zahira Khairunnisa; Zaid Al Qodhi (Al-Kindi, 2026)
This journal aims to describe strategic management and strategic planning in Islamic education, analyze Islamic perspectives on such planning, and identify challenges in its implementation, in order to help educational institutions face the dynamics of globalization. The method used is a descriptive-qualitative literature study through literature analysis, mapping of concepts such as vision-mission, SWOT analysis, strategy formulation, implementation, evaluation, and review of Quranic verses (QS. Al-Anfal: 60) and hadith about leadership responsibilities. The results of the study show that strategic management includes a continuous process for the adaptation of institutions with Islamic values, strategic planning functions as an efficient and holistic 3-5-year Strategic Plan guideline, but the main challenges include limited human resources, visionary leadership, resistance to change, minimal funds, and external influences such as globalization, so that it is necessary to improve competencies and routine evaluations for the sustainability of Quranic education.